(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2013)
A novel type of elementary osmotic pump [EOP] tablet for efficient delivery of poorly water-soluble drug, glipizide has been designed. Drug release from the system, called Swellable Elementary Osmotic Pump [SEOP], is through a delivery orifice in the form of a very fine dispersion, ready for dissolution and absorption. SEOP tablets were prepared by compressing the mixture of micronized drug and excipients into convex tablet. The effect of wetting agent, swelling agent, osmotic agent and hydrophobic plasticizer on the release rate were investigated. The release behavior of glipizide from different formulations of this dosage forms were studied at pH 6.8 for a period of 24 hours. The drug release profile from osmotic devices showed that the type of polymer in the core formulation can markedly affect the drug release. When the amount of HPMC E50-LV was increased from 30 to 60 mg, decrease in drug release was observed. Increasing the amount of wetting agent to an optimum level of 45 mg significantly increased the release rate and improved zero order release pattern of glipizide. Increasing the concentration of Dibutylphthalate [DBP-30%] in the semi permeable membrane of the device retarded the release rate of glipizide but gave best results at the 20% concentration. Based on the SEM studies, optimized orifice diameter was found to be 500µm. Compared with the marketed Glipizide extended release tablet; GF2 gave the best release rate for 24 hours. The bioavailability studies for glipizide SEOP and Glipizide extended release tablet was carried out in albino rabbits and there was a good in-vivo and in-vitro correlation for GF2 as shown by the higher Cmax and AUC values. Thus a novel SEOP was successfully formulated for glipizide to achieve zero order drug release over a period of 24 hours.